(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The country’s response to a potential outbreak may benefit greatly from the practical knowledge, experience and skills of paramedical students in a number of ways. Thus, this study was conducted to evaluate attitude and practices regarding COVID-19 among paramedical students studying in different colleges of Janakpurdham, Nepal. MATERIALS AND METHODS: A structured questionnaire was used in a descriptive cross-sectional study to collect information on COVID-19 attitude and practices among HA students enrolled in different selected colleges affiliated to Council for Technical Education and Vocational Training (CTEVT), Nepal in April and May of 2022. Statistical Package for the Social Sciences was used to analyse the data. Significant results were defined as a p-value of less than 0.05. RESULTS: Majority of girls from NHRDA and MTA (53.7% and 50.58%) respectively, believed that COVID-19 infection is a global problem than CMC girls (35.08%). Of 63.5% and 49.35% girls from NHRDA and MTA agreed that the public is crucial for infection control. More than 60% of girls from NHRDA and MTA suffered from mild fever after immunization fall down by 52.17% girls from CMC’s while 52.3%, 30.6% and 42.42% girls from each college respectively felt 4healthy after immunization and one fourth of total suffered from high fever after immunization. The significant association between the COVID-19 immunization among the students of different colleges (p = 0.00). CONCLUSIONS: Most of the girl students had positive attitude and optimistic practice, while the boys followed appropriate safety measures to avoid contracting COVID-19. A significant correlation has been found between students from various colleges and the COVID-19 vaccine.